2023
DOI: 10.1002/ece3.9718
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal flooding decreases fruit‐feeding butterfly species dominance and increases spatial turnover in floodplain forests of central Amazonia

Abstract: The seasonal flood pulse in Amazonia can be considered a primary driver of community structure in floodplain environments. Although this natural periodic disturbance is part of the landscape dynamics, the seasonal inundation presents a considerable challenge to organisms that inhabit floodplain forests. The present study investigated the effect of seasonal flooding on fruit‐feeding butterfly assemblages in different forest types and strata in central Amazonia. We sampled fruit‐feeding butterflies in the canopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…(Euphorbiaceae) in a floodplain forest at the Teles Pires river, not far from the Cristalino Lodge [94]. Both this and previous studies have found satyr species to be indicators of or particularly common in floodplain forests, probably because these butterflies feed on fast-growing grasses that occur in such forests during the dry season [36][37][38]. Finally, it is interesting to note that the genus Calycopis belongs to a group of detritivorous Lycaenidae, whose larvae are capable of feeding on dead leaves on the ground [95][96][97].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…(Euphorbiaceae) in a floodplain forest at the Teles Pires river, not far from the Cristalino Lodge [94]. Both this and previous studies have found satyr species to be indicators of or particularly common in floodplain forests, probably because these butterflies feed on fast-growing grasses that occur in such forests during the dry season [36][37][38]. Finally, it is interesting to note that the genus Calycopis belongs to a group of detritivorous Lycaenidae, whose larvae are capable of feeding on dead leaves on the ground [95][96][97].…”
Section: Discussionmentioning
confidence: 62%
“…Butterfly assemblages have been shown to differ between floodplain and terra firme forests in Amazonia, with the flooding acting as an environmental filter [36][37][38]. Contrary to várzea forests, which receive nutrient input from the inundation by muddy water and therefore are highly productive, igapó forests are flooded by poor, acidic black-waters, and are comparatively species-poor and unproductive [91][92][93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation